The potential biological activities of Aspergillus luchuensis-aided green synthesis of silver nanoparticles - Abd Elghaffar, Rasha Y.; Emam, Amany M.; Taher, Ehab S.; Baz, Mohamed M.; Nayel, Hamada; Abdeen, Ahmed; El-Nablaway, Mohammad; Alwutayd, Khairiah M.; Mihaela, Ostan; Ioan, Banatean-Dunea; Khattab, Abeer A.; Al‑Serwi, Rasha H.; et al. (Frontiers in Microbiology, 2024)
Biosynthetic metals have attracted global attention because of their safety, affordability, and environmental friendliness. As a consequence, the cell-free filtrate (CFF) of Dill leaf-derived endophytic fungus Aspergillus luchuensis was employed for the extracellularly synthesis silver nanoparticles (AgNPs). A reddish-brown color shift confirmed that AgNPs were successfully produced. The obtained AgNPs were characterized by UV-Vis (ultraviolet-visible spectroscopy), Transmission electron microscopy (TEM), FTIR, EDX, and zeta potential. Results demonstrated the creation of crystalline AgNPs with a spherical shape at 427.81 nm in the UV-Vis spectrum, and size ranged from 16 to 18 nm as observed by TEM. Additionally, the biogenic AgNPs had a promising antibacterial activity versus multidrug-resistant bacteria, notably, S. aureus, E. coli, and S. typhi. The highest growth reduction was recorded in the case of E. coli. Furthermore, the biosynthesized AgNPs demonstrated potent antifungal potential versus a variety of harmful fungi. The maximum growth inhibition was evaluated from A. brasinsilles, followed by C. albicans as compared to cell-free extract and AgNO3. In addition, data revealed that AgNPs possess powerful antioxidant activity, and their ability to scavenge radicals increased from 33.0% to 85.1% with an increment in their concentration from 3.9 to 1000 µg/mL. Furthermore, data showed that AgNPs displayed high catalytic activity of safranin under light irradiation. The maximum decolorization percentage (100%) was observed after 6 h. Besides, the biosynthesized AgNPs showed high insecticidal potential against 3 rd larval instar of Culex pipiens. Taken together, data suggested that endophytic fungus, A. luchuensis, is an attractive candidate as an environmentally sustainable and friendly fungal nanofactory.